2018
DOI: 10.3116/16091833/19/2/106/2018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phytoplankton species using Hermite transform

Abstract: Abstract. We apply a Hermite transform joint with a classical correlation analysis to successfully recognize phytoplankton species even in such complicated cases when the relevant images reveal the patterns of inhomogeneous illumination and natural distortions. The images of phytoplankton species are divided into two groups consisting of 30 samples each. Those belonging to the first group are the images with neither inhomogeneous illumination nor noise, while the second one embraces the images with the backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The first case consisted of doing the conventional correlation, which takes the input images, then applied the Fourier transform to the images, do the point-by-point multiplication, applied the inverse Fourier transform to the result and, finally obtain the correlation plane. The second case was using the Hermite transform L 1,1 with which better correlation values are obtained [39], in this case, the input images are modified using the Hermite transform before applying the Fourier transform and do the correlation. In the third case, the fractional Hermite transform with the optimal order was used for each image before the Fourier transform.…”
Section: Methodsmentioning
confidence: 99%
“…The first case consisted of doing the conventional correlation, which takes the input images, then applied the Fourier transform to the images, do the point-by-point multiplication, applied the inverse Fourier transform to the result and, finally obtain the correlation plane. The second case was using the Hermite transform L 1,1 with which better correlation values are obtained [39], in this case, the input images are modified using the Hermite transform before applying the Fourier transform and do the correlation. In the third case, the fractional Hermite transform with the optimal order was used for each image before the Fourier transform.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 6 shows an example of the Hermite transform of an image of a melanoma lesion, considering the transform order. In recent work, Castro-Valdez and Álvarez-Borrego [22], used the Hermite transform joint to classical correlation to recognize phytoplankton species and based on the noise in the output correlation plane, demonstrated that the optimal order of the Hermite transform is L 1,1 .…”
Section: The Hermite Transformmentioning
confidence: 99%